Heterogeneity of the sediment oxygen demand and its contribution to the hypoxia off the Changjiang estuary and its adjacent waters. (November 2021) - Chi, Lianbao; Song, Xiuxian; Ding, Yu; Yuan, Yongquan; Wang, Wentao; Cao, Xihua; Wu, Zaixing; Yu, Zhiming
Abstract: The severe hypoxia off the Changjiang estuary (CE) has a dual-core structure, and the two hypoxic zones exhibit behavioural, physical and biochemical differences. Currently, few studies have revealed straightforward differences regarding the key biochemical processes between these two hypoxic zones. In this study, the phytoplankton sinking rate (PSR) and sediment oxygen demand (SOD) were measured by field experiments and compared between the two hypoxic regions. PSR and SOD ranged from 0.75–3.34 m day −1 and 5.67–16.19 mmol m −2  day −1, respectively. Interestingly, PSR and SOD were higher in the southern region than in the northern region, implying stronger pelagic-benthic biogeochemical coupling in the southern region. SOD accounted for approximately 44% and 51% of DO net consumption in the northern and southern regions, respectively, from July to August. The southern hypoxic region appeared to exhibit intense DO consumption and fast DO supplementation, while the northern hypoxic region seemed to exhibit slow DO consumption and supplementation. Graphical abstract: Unlabelled Image Highlights: PSR and SOD off the Changjiang estuary were quantified via incubation experiments. PSR and SOD were identified as important contributors to the formation of hypoxia. Co-occurrence of high PSR and high SOD was observed in the southern hypoxic region.